Profil Fitokimia Simplisia dan Ekstrak Etanol Daun Kedondong Pagar (Lannea coromandelica (Houtt.) Merr.) sebagai Tanaman Obat - Safriana Safriana; Andilala Andilala; Cut Fatimah; Samrani Samrani (Fakultas Farmasi Universitas Pancasila, 2021)
Lannea coromandelica (Houtt.) Merr., or known as Kedongdong Pagar in Indonesia, family Anacardiaceae, Kedongdong Pagar leaves that has been proved by some villagers of Samakurok, Tanah Jambo Aye district, Northen Aceh, NAD, who consume boiled water of kedongdong pagar leaves to lower blood glucose levels. This study was to determine the class of chemical compounds contained in simplicia and ethanol extracts of the kedongdong pagar leaves from phytochemical screening results. The results of phytochemical screening showed that chemical compounds contained in simplicia and extracts of kedongdong pagar leaves were flavonoids, saponins, glycosides, tannins and steroids/triterpenoids. Based on the studies that have been carried out, Kedongdong Pagar leaves have great potential to be researched and further developed to become one of the sources of medicinal plants in Indonesia.